Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1097/rlu.0000000000002649
|View full text |Cite
|
Sign up to set email alerts
|

EBV-Associated T-Cell Lymphoproliferative Disorders Demonstrated on FDG PET/CT in a Patient With Hemophagocytic Lymphohistiocytosis

Abstract: FDG PET/CT was performed in a 20-year-old woman to find the underlying cause of hemophagocytic lymphohistiocytosis. The images revealed hypermetabolic activity in multiple lymph nodes and in the spleen. Lymphoma was suspected. However, the pathology of bone marrow, lymph nodes, and the spleen demonstrated chronic active Epstein-Barr virus–associated T-cell lymphoproliferative disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…However, some studies found that the extranodal NK/T-cell lymphoma nasal type, aggressive NK cell leukemia, and some types of B-cell lymphoma occasionally lack lesions with focal FDG uptake [ 9 12 19 ]. Multiple hypermetabolic lymph nodes or patchy bone lesions were observed in several cases of EBV-associated HLH [ 12 21 22 23 ]. In the absence of EBV infection, lesions with focal FDG uptake in the bone marrow are a reliable sign of malignancy in secondary HLH.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies found that the extranodal NK/T-cell lymphoma nasal type, aggressive NK cell leukemia, and some types of B-cell lymphoma occasionally lack lesions with focal FDG uptake [ 9 12 19 ]. Multiple hypermetabolic lymph nodes or patchy bone lesions were observed in several cases of EBV-associated HLH [ 12 21 22 23 ]. In the absence of EBV infection, lesions with focal FDG uptake in the bone marrow are a reliable sign of malignancy in secondary HLH.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics quantified the spatial complexity of them. This study exhibited that the heterogeneity of spleen and liver may reveal overproliferation of immune cells accompanied with inflammatory infiltration triggered by EBV infection (37)(38)(39)(40). On the other hand, the heterogeneous distribution of metabolism or density may also suggest the involvement of tumor cells (41)(42)(43).…”
Section: Timely Diagnosis and Prognosis Are Critical For Hlh Considering That The Early And Proper Administration Of An Efficaciousmentioning
confidence: 87%
“…The difference may result from the high physiological uptake in children's cervical lymph nodes and the large proportion of EBV infection-related lymphoproliferative diseases (EBV-LPD) in children's HLH. As LPD is often associated with multiple enlarged lymph nodes with increased FDG uptake, as well as focal hypermetabolism sometimes, it is challenging to differentiate LPD from lymphoma [ 11 ]. In this study, two patients with intestinal involvement were pathologically diagnosed with Hodgkin's lymphoma and non-Hodgkin's lymphoma.…”
Section: Discussionmentioning
confidence: 99%